The Influence of Literacy Programs and the Availability of Learning Resources on Students' Literacy Abilities Through Student Involvement - Pita Alfiyatu Khasanah; Athok Fu’adi (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
The literacy skills of students in Indonesia still face challenges despite the increase in PISA rankings, because literacy programs are not yet fully effective, and the limitations of varied learning resources. The purpose of this research is to analyze the influence of literacy programs and the availability of learning resources on students' literacy skills, as well as to examine the role of student involvement as a mediator in these relationships. The research method uses a quantitative approach with an explanatory-correlational design through the analysis of Partial Least Squares Structural Equation Modeling (PLS-SEM) using a sample of 173 grade XI students of SMAN 1 Mejayan who were selected by simple random sampling and data collection through a Likert scale questionnaire. The results of the study showed that literacy programs, the availability of learning resources, and student involvement had a positive and significant effect on literacy skills, but student involvement was not proven to be significant as a mediator. These findings confirm that improving literacy can be achieved through literacy programs that are integrated into learning and the provision of varied learning resources, both print and digital, with recommendations for schools and teachers to design more flexible and contextual literacy strategies. The novelty of this research lies in a conceptual model that tests student involvement as a mediating variable, thus providing a new picture of the implementation of literacy strategies in secondary schools in Indonesia